Pelatihan Pembuatan E-book dan Soal Berbasis HOTs Interaktif untuk Meningkatkan Kemampuan Literasi Digital Guru SMP YPK Merauke - Uspayanti, Rezky; Pandiangan, Nurlela (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to improve the digital literacy skills of the teachers in SMP YPK Merauke through training in making e-books using the SIGIL application and interactive HOTs questions using Socrative. Implementing this service used training and mentoring based on partner needs. The instrument for evaluating this activity used a questionnaire consisting of 12 statements and was analyzed descriptively. The results of this activity showed that the teachers of SMP YPK Merauke created an interactive e-book using the SIGIL application, which contained not only pictures and text but also video and audio that could make it easier for students to understand the material and increase students’ interest in learning. In addition, teachers at SMP YPK Merauke could compile interactive HOTs questions using Socrative, which consisted of questions in the form of multiple choices, true-false, and short answers. They could apply the questions in socrative in the teaching and learning process.